Bioactive Compounds from Extremophiles Genomic Studies, Biosynthetic Gene Clusters, and New Dereplication Methods - Giddings, Lesley-Ann. (Extremophilic Bacteria,, 2015)
This SpringerBrief sheds new light on bioactive materials from extremophiles with the focus on the biosynthesis processes and related genomics. It deals with all aspects of the chemical compounds produced by organisms living under extreme conditions that may have potential as drugs or lead to novel drugs for human use.